Journalscan (Res Medica, 2014)
This is a short collection of interesting items pertinent to medicine and science in general. It gives a taste of some of the current work in hand around the world. We would welcome any contributions of this nature, just a short chatty narrative of an interesting or amusing article that you have seen or read.